2003
DOI: 10.1159/000071117
|View full text |Cite
|
Sign up to set email alerts
|

Independent Predictors of Late Hydrocephalus in Patients with Aneurysmal Subarachnoid Hemorrhage – Analysis by Multivariate Logistic Regression Model

Abstract: Object: We determined independent variables contributing to the development of late hydrocephalus after subarachnoid hemorrhage (SAH). Methods: A total of 114 consecutive patients who underwent surgery for aneurysms within 72 h after SAH were studied. Thirty-nine patients underwent ventriculoperitoneal shunt (VPS) placement (14 patients within 30 days and 25 patients more than 30 days after onset). Univariate and multivariate analyses were performed to assess relationships among various variables and shunt pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 14 publications
3
33
2
Order By: Relevance
“…The mortality rate has been reported to be as high as 42.6–83.3% [16], the mortality rate of surgery 35.7–100% [17]. When the IVH is large enough to impede normal cerebrospinal fluid circulation, acute obstructive hydrocephalus can occur in the subacute and chronic stages of IVH, communicating hydrocephalus may develop if fibrosis of the basal leptomeninges occurs or reabsorption of CSF becomes impaired from fibrosis of the arachnoid villus [18,19,20,21,22]. Although there have been some medical or surgical therapies for IVH, none of them are encouraged.…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate has been reported to be as high as 42.6–83.3% [16], the mortality rate of surgery 35.7–100% [17]. When the IVH is large enough to impede normal cerebrospinal fluid circulation, acute obstructive hydrocephalus can occur in the subacute and chronic stages of IVH, communicating hydrocephalus may develop if fibrosis of the basal leptomeninges occurs or reabsorption of CSF becomes impaired from fibrosis of the arachnoid villus [18,19,20,21,22]. Although there have been some medical or surgical therapies for IVH, none of them are encouraged.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic hydrocephalus after aneurysmal SAH that impairs cerebrospinal fluid (CSF) dynamics and therefore requires a permanent CSF diversion is called ‘shunt-dependent chronic hydrocephalus'. Several previous studies have identified multiple factors, such as increased age, female sex, poor Hunt and Hess (H&H) grade, acute hydrocephalus, distal posterior circulation aneurysms, cerebral vasospasm, antifibrinolytic therapy, and intraventricular haemorrhage (IVH), that could predict the need for permanent CSF diversion [1,4,6,7,8,9]. However, the link between fever and shunt-dependent hydrocephalus remains poorly understood [10].…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of sequential changes of oxyhemoglobin concentration showed decreases by day 5 and maintenance at a very low level with urokinase irrigation, but increases peaking on day 9 without urokinase irrigation. 13) Our previous report 9) and others 1,12,15) have indicated that duration of CSF drainage is a statistically significant predictor of late hydrocephalus after SAH. Continuous CSF drainage may promote occlusion of physiological CSF pathways.…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, intermittent CSF drainage has been suggested to keep the normal subarachnoid space open, because intermittent CSF pressure is an effective force in preventing the formation of occlusive membranes and clots. 11) Our previous study 9) showed that brain damage due to intraoperative manipulation and cerebral vasospasm is involved in the pathogenesis of late hydrocephalus. Excessive drainage of CSF is related to a greater incidence of cerebral infarction and occurrence of late hydrocephalus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation